H2, N2, CO2, and CH4 unary adsorption isotherm measurements at low and high pressures on zeolitic imidazolate framework ZIF-8 - Hwang,J; Azzan,H; Pini,R; Petit,C (Journal of Chemical & Engineering Data, 2022)
Excess adsorption of CO2, CH4, N2, and H2 on ZIF-8 was measured gravimetrically in the pressure range ranging from vacuum to 30 MPa at 298.15, 313.15, 333.15, 353.15, and 394.15 K using a magnetic suspension balance. The textural properties of the adsorbent materiali.e., skeletal density, surface area, pore volume, and pore-size distributionwere estimated by helium gravimetry and N2 (77 K) physisorption. The adsorption isotherms were fitted with the Sips isotherm model and the virial equation, and the values of isosteric heat of adsorption and Henry constants for the gases were determined using the latter.